POLIMORFISME GEN ANGIOTENSIN CONVERTING ENZYME ACE ID PADA PENDERITA MIGREN - Hasmawaty Basir (NEURONA, 2013)
INTRODUCTION MIGRAINE IS A NEUROVASCULAR DISEASE CHARACTERIZED BY HEADACHE AND NEUROLOGIC SYMPTOMS COMBINED WITH AUTONOMIC AND GASTROINTESTINAL PROBLEM THE PATHOPHYSIOLOGY OF MIGRAINE IS NOT ENTIRELY CLEAR YET AND THE ROLE OF GENETICS IS STILL CONTROVERSIAL ONE OF THE GENES DISORDER NOT WIDELY STUDIED IS ANGIOTENSINCONVERTING ENZYME ACE GENE POLYMORPHISM THE ROLE OF THIS GENE IN THE PATHOPHYSIOLOGY OF MIGRAINE IS STILL CONTROVERSIAL WEATHER DD GENOTYPE INCREASED IN MIGRAINE WITH OR WITHOUT AURA